ANALISIS KANDUNGAN LOGAM Pb, Cu, Cd DAN Zn PADA SAYURAN SAWI, KANGKUNG DAN BAYAM DI AREAL PERTANIAN DAN INDUSTRI DESA PAYA RUMPUT TITIPAPAN MEDAN - Muhammad Yusuf; Kiki Nurtjahja; Rosliana Lubis (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
The levels of Pb, Cu, Cd and Zn in sawi (Barsssica rapa), ground kuna (Ipomea reptans), and spinach (Amaranthus tricolor) in the area of Paya Rumput Titipapan Medan village have been done. The goal is to know the levels of these metals in vegetables grown in the agricultural area of Paya Rumput Titipapan Village. Samples taken randomly in wash drained and weighed. Wet weight then dried at a temperature of 50-100o C for 3 hours, After dry on weigh in gerus until smooth. The sample was destructed with concentrated nitric acid with temperature 80o C, the sample was analyzed by using atomic absorption spectrophotometric (AAS). The results showed the highest levels of lead found in spinach is 6 mg / kg. Levels of cadmium in kale and spinach is 3 mg / kg. While the Cu content on the analysis results are still within the maximum limit. The concentration of Pb, Cd, Zn in each sample exceeds the maximum allowed by the Decree of Dit Jend POM No 03725 / B / SKVII / 89 and SNI 7387: 2009.